FACTORS AFFECTING SUCCESSFUL PULMONARY TUBERCULOSIS TREATMENT AT STABAT HEALTH CENTER IN LANGKAT DISTRICT - Nahdhia; Sinaga, Bintang Yinke Magdalena; Adriztina, Indri; Saragih, Rina Amalia Caromina; Nasution, Tetty Aman (TALENTA Publisher, Universitas Sumatera Utara, 2025)
Background: Pulmonary Tuberculosis (TB) is a significant global public health problem, mainly affecting the lungs. Many factors are associated with the successful treatment of pulmonary TB patients. This study aims to analyze factors affecting the successful treatment of pulmonary TB at Stabat Health Center, Langkat District. Method: This observational analytic study used a cross-sectional design and was conducted from October 2024 to January 2025 at Stabat Health Center. All pulmonary TB patients diagnosed between 2022 and 2023 who met the inclusion and exclusion criteria were included using a total sampling approach. Data were collected from the Tuberculosis Information System and analyzed using univariate, bivariate, and multivariate analyses. Results: Comorbid diabetes mellitus (DM) (p=0.003; OR=7.01) and distance to health facility (p=0.022; OR=4.44) were significantly associated with treatment success. In contrast, age, sex, occupation, comorbid HIV infection, and treatment status did not show a statistically significant association with treatment outcomes. Conclusion: Comorbid DM had the greatest effect on successful of pulmonary TB treatment at Stabat Health Center. TB patients with Diabetes Mellitus comorbid need special attention. Further research is needed to analyze other potential factors.